2020
DOI: 10.1002/anie.202005785
|View full text |Cite
|
Sign up to set email alerts
|

ACQ‐to‐AIE Transformation: Tuning Molecular Packing by Regioisomerization for Two‐Photon NIR Bioimaging

Abstract: The traditional design strategies for highly bright solid‐state luminescent materials rely on weakening the intermolecular π–π interactions, which may limit diversity when developing new materials. Herein, we propose a strategy of tuning the molecular packing mode by regioisomerization to regulate the solid‐state fluorescence. TBP‐e‐TPA with a molecular rotor in the end position of a planar core adopts a long‐range cofacial packing mode, which in the solid state is almost non‐emissive. By shifting molecular ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(84 citation statements)
references
References 55 publications
0
84
0
Order By: Relevance
“…d) Single crystal structure, e) dimer structure, and f) molecular p-p stacking structures TBP-e-TPA. [25] Angewandte Chemie Zuschriften fluorescence signals (collected from 700-800 nm) from twophoton imaging irradiated by a NIR-II pulsed laser at 1040 nm displayed almost identical distribution with that of one-photon imaging (Figure 4 c). It was widely reported that 2PF microscopy (2PFM) shows greater penetration depth, lower photodamage, and better 3D resolution compared to one-photon microscopy.…”
Section: Angewandte Chemiementioning
confidence: 74%
“…d) Single crystal structure, e) dimer structure, and f) molecular p-p stacking structures TBP-e-TPA. [25] Angewandte Chemie Zuschriften fluorescence signals (collected from 700-800 nm) from twophoton imaging irradiated by a NIR-II pulsed laser at 1040 nm displayed almost identical distribution with that of one-photon imaging (Figure 4 c). It was widely reported that 2PF microscopy (2PFM) shows greater penetration depth, lower photodamage, and better 3D resolution compared to one-photon microscopy.…”
Section: Angewandte Chemiementioning
confidence: 74%
“…Various design strategies have been explored to create AIE agents with high ROS generating efficiency. 72,73 For example, a strong electron donor-acceptor interaction in the molecular skeleton facilitates ICT, thus leading to the enhanced singlet oxygen generation efficacy. 74 Based on these design strategies, Tang et al74 synthesized several zwitterionic compounds, BITT, BITB, ITT, and ITB, which consist of a dimethylaniline or triphenylamine moiety as the donor, thiophene fragment as a donor and π-bridge, double bond for the π-bridge, and a quaternary ammonium salt unit as acceptor.…”
Section: Aie Agents With Ros Generating Abilitymentioning
confidence: 99%
“…The basic framework of the molecules consisted of the Dithieno[2,3‐a:3′,2′‐c]benzo[i]phenazine (TBP) and the twisted molecular rotor TPA. [ 170 ] From the TBP‐ e ‐TPA molecule with long‐range cofacial packing mode to the TBP‐ b ‐TPA with discrete cross packing mode (Figure 7(H)), the minor modification of the positions of TBP units arose the switch from ACQ to AIE due to the generation of steric hindrance. The AIE active TBP‐ b ‐TPA also expressed the marvelous 2PA property (Figure 7(I)).…”
Section: Aie Materials For Nlomentioning
confidence: 99%